2011
DOI: 10.1080/13636820.2011.622447
|View full text |Cite
|
Sign up to set email alerts
|

‘What with your grades?’ Students’ motivation for and experiences of vocational courses in further education

Abstract: IntroductionIncreased funding for vocational qualifications (BIS, 2010) as well as vocational qualifications that are understood and valued by employers underpins one of the new coalition government's key aims of better vocational training for teenagers [Cabinet Office, 2010]. Whilst the future of the Diplomas may be in doubt, a commitment to vocational courses emphasises the overall recognition that the UK needs to both develop its vocationally trained workforce as well as provide alternative post-16 educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…(Sarina) Other participants also placed particular value on GCSEs or thought that not having them would limit their college options. These accounts resonate with those offered by the young people in Fuller and Macfadyen (2012) study who viewed the vocational qualifications they were working towards as second best. The authors make an important point when they conclude that, 'Only when traditional and non-traditional educational routes have parity can vocational courses be seen as an option that is not just for educational underachievers' (p. 99).…”
Section: Critical Studies In Educationmentioning
confidence: 76%
See 1 more Smart Citation
“…(Sarina) Other participants also placed particular value on GCSEs or thought that not having them would limit their college options. These accounts resonate with those offered by the young people in Fuller and Macfadyen (2012) study who viewed the vocational qualifications they were working towards as second best. The authors make an important point when they conclude that, 'Only when traditional and non-traditional educational routes have parity can vocational courses be seen as an option that is not just for educational underachievers' (p. 99).…”
Section: Critical Studies In Educationmentioning
confidence: 76%
“…The smaller, less formal settings, tailored programmes of study and more respectful relationships between staff and students have all been identified as important contributing factors (Fuller & Macfadyen, 2012;Mills, Renshaw, & Zipin, 2013). However, educational alternatives have also been criticised for offering only low-level qualifications that do not necessarily support higher level academic study (Fuller & Macfadyen, 2012;Simmons, Thompson, & Russell, 2014), for overlooking the needs of girls where they are outnumbered by boys (Fuller & Macfadyen, 2012;Osler & Vincent, 2003), and for providing schools with an easy opt-out that removes the need to examine the systemic and institutional barriers that lead to disaffection among some students (Mills et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to impact on disaffection, vocational learning is used to improve attitudes to learning with the effect of reengagement in school emanating from a student's choice to participate (Davies and Biesta 2007). This is important as young people need to value their learning (Fuller and Macfadyen 2012). School disaffection, then, can reduce through the opportunity for students to experience alternative learning where school links are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, attitude is conceptualised as a crucial factor in disaffection in that it is related to choice, whereby disengagement is arguably an agentic student action. Furthermore, education needs to be valued by young people (Fuller and Macfadyen 2012), and this can impact on attitude and, subsequently, engagement.…”
Section: Vocational Learningmentioning
confidence: 99%
“…Research by the Slack, Hughes and Rout (2013) also found that students predicted to do well at GCSE were less likely to receive advice about vocational options, while those predicted to do less well were more likely to. In addition, students often have a sense that one route is more preferable for them than others, dependent on how they identify in relation to their understanding of themselves as educational 'achievers' or not (Fuller 2009;Fuller and Macfadyen 2012).…”
Section: Context and Backgroundmentioning
confidence: 99%